TECHNOLOGICAL INTEGRITY AND ABRASION MANAGEMENT AT THE KUTA BEACH TOURIST ATTRACTION - Gede Agung Widana, Ida Bgs; Triana Wulandari, Komang; Pramana, I Gede Wisma; Satria Dharma Putra, I Kadek; Wira Dipta Kusuma, I Kadek; try suryadinatha, I Komang (JURNAL KEPARIWISATAAN, 2025)
Coastal erosion at Kuta Beach, Bali, represents an increasingly intense and complex ecological crisis resulting from a combination of natural factors and human activities. The degradation of the shoreline not only impacts public infrastructure but also threatens the sustainability of social, cultural, and economic spaces of coastal communities. Previous mitigation efforts, such as beach nourishment and the construction of breakwaters, have shown limited effectiveness and have not been accompanied by community-based or adaptive technological approaches. This study aims to evaluate past responses and develop participatory and sustainable intervention strategies. Using a descriptive qualitative approach, data were obtained through literature review, field observation, and interpretation of scientific sources. The findings reveal that addressing coastal erosion at Kuta Beach requires a collaborative action model that is not only technically driven but also strengthens disaster communication systems, public education, and tourism-friendly technologies. The proposed recommendation is the KUTA COASTAL GUARD program, which integrates technical actions, socio-cultural engagement, environmental literacy, and citizen-based monitoring. Technological supports such as the SISI application, Submerged Pneumatic Barrier, and Reef Ball are also identified as potential solutions to preserve the ecological and recreational functions of the beach. This study highlights the importance of shifting from reactive approaches toward adaptive, cross-sectoral, and replicable crisis management for other coastal areas.